MANAJEMEN PENDIDIKAN KARAKTER (STUDI KASUS DI MADRASAH TSANAWIYAH NAHDLATUL ULAMA SUMBERASRI KECAMATAN PURWOHARJO KABUPATEN BANYUWANGI) - Al Muftiyah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2017)
MTS. NU is one madrasa that has your attention on character education program by doing some conditioning-good conditioning activities conducted at the madrasa. This research uses qualitative descriptive method approach to analysis through design case studies. As for the results of this research include: from the aspect of planning include: a) designing conditions of madrasah conducive, b) designing curriculum character education in ekplisit, c) creates the curriculum of integrative character, d) classroom management, e) environmental management beyond the classroom. In its implementation, including: a) collaboration between the citizens of the school, b) apply the example, c) conditioning prayers in congregation, d) coaching intensive Quran, e) appreciate the creativity of learners, f) harmonious relationship between teachers and learners. And in evalusi: a) in collaboration with the elderly learners (co parenting), b) watchful eye against morals, c) home visit.